Perceptions of UIN SYAHADA Padangsidimpuan Students Toward Bank Jago Syariah - Mubarok, Arif; Abdul Kader, Fadel Kakkidi; Lubis, Nuraswani (Journal of Islamic Financial Technology, 2023)
This research aims to identify and analyze the perceptions of UIN SYAHADA Padangsidimpuan students towards Bank Jago Syariah, a banking institution that operates based on sharia principles. The background to this research focuses on the importance of understanding and accepting sharia banking products and services among the younger generation, especially students who have great potential to become future customers. The discussion of this research is related to perception, with an approach using theories related to Bank Jago Syariah, such as the concept of perception according to Yasir, quoted from Kenneth A. Sereno and Edward M., as a process of receiving and analyzing information related to Bank Jago Syariah. This research method is descriptive qualitative using primary and secondary data. The research subjects were students from the Faculty of Islamic Economics and Business at UIN SYAHADA Padangsidimpuan, with data collection techniques through direct interviews.The research results showed that some students welcomed the presence of Bank Jago Syariah, considering it to have a positive impact, while others did not know about the existence of digital-based Bank Jago Syariah.